2018
DOI: 10.1155/2018/7263849
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Antimicrobial Resistance ofNeisseria gonorrhoeaein a Moroccan Area

Abstract: Objectives To identify the prevalence and the types of Neisseria gonorrhoeae (NG) resistance plasmids-mediated penicillin (PPNG) and tetracycline (TRNG), the ciprofloxacin resistance (CRNG), and related risk factors of each types of resistance. Methods The beta-lactamase-producing plasmid types (Africa, Asia, and Toronto), tetM tetracycline resistance plasmid types (America and Dutch), and the determination of the Ser-91 mutation of GyrA were detected by specifics PCRs on 149 diagnosed NG positives samples fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…In a cohort of pregnant women from Australia, predictors of being infected with N. gonorrhoeae included young age, harmful alcohol use, unwanted pregnancy, low birth weight, perinatal death, and coinfection with other STIs during pregnancy [25]. Other studies have also shown significant associations with sociodemographic, behavioural, and clinical factors and N. gonorrhoeae infection [24,26]. However, our study showed no statistical significance with sociodemographic, behavioural, and clinical factors in relation to N. gonorrhoeae infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cohort of pregnant women from Australia, predictors of being infected with N. gonorrhoeae included young age, harmful alcohol use, unwanted pregnancy, low birth weight, perinatal death, and coinfection with other STIs during pregnancy [25]. Other studies have also shown significant associations with sociodemographic, behavioural, and clinical factors and N. gonorrhoeae infection [24,26]. However, our study showed no statistical significance with sociodemographic, behavioural, and clinical factors in relation to N. gonorrhoeae infection.…”
Section: Discussionmentioning
confidence: 99%
“…Neisseria gonorrhoeae is the second most prevalent bacterial sexually transmitted infection (STI) and is a major cause of mortality and morbidity [1]. A global STI surveillance in 2018 was conducted by the World Health Organization (WHO) and revealed an estimated 87 million new gonorrhoea infections globally during 2016, with an incidence of 20 cases per 1000 population (uncertainty interval [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] in women [2]. A study conducted in South Africa and Zimbabwe reported an overall prevalence of 0.7% for N. gonorrhoeae infections in women from the general population [3].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown an association between the prevalence of N. gonorrhoeae infections and socio-demographic, behavioural and clinical factors. A study conducted by Karim et al 16 revealed a high prevalence of N. gonorrhoeae in unmarried, educated and urbanised women, suggesting that socio-demographic, behavioural and clinical factors do play a role in the spread of this infection. The current study showed that there is no statistical significance between the socio-demographic and behavioural factors in relation to prevalence (Supplementary data, Appendix 1, Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Direct Hinf1 digestion of PCR product have been used by many researchers to screen GyrA and ParC genes mutations in different bacteria; S. pneumoniae at positions serine (83) of GyrA and serine (79) of ParC 22 , A. baumannii at positions gyrA (codons 83 and 87) and parC (codons 80 and 84) 23 and N. gonorrhoeae at positions Ser (91) of GyrA 24 were all found significantly associated with ciprofloxacin resistance.…”
Section: Discussionmentioning
confidence: 99%